Is biogas an energy or a sustainability product? - Business opportunities in the Finnish biogas branch. (1st October 2019) - Winquist, Erika; Rikkonen, Pasi; Pyysiäinen, Jarkko; Varho, Vilja
Abstract: The business opportunities in the Finnish biogas branch were studied through policy document analysis, analysis of the financial performance, and interviews of the biogas companies (in industrial and farm-scales). Although our study focuses on the case of Finland, many identified features of biogas production can be recognized at least on a European level. The analysis of national policy documents (related to biogas and renewable energy) revealed that even if biogas production and utilization is encouraged, all objectives and measures are rather cautiously formulated and tend to remain on a general level. In addition, economic arguments in policy documents (cost-effectiveness, commercial and business potential, market principles) are emphasized as common criteria for renewable energy technologies, biogas included. The financial performance was studied during 2011–2017 when biogas production more than doubled in Finland (from 52 000 m 3 to 110 000 m 3 ). While biogas production is not, in fact, economically very lucrative (the return on investment (ROI) of the studied companies has decreased from 10% to 5% during 2011–2017), there are other partially nonmarket benefits that support biogas production. The larger scale industrial plants' performance was more stable, most probably due to the gate fees which they obtained from waste treatment. Based on the interviews, the farm-scale plants gained also nonmarket cobenefits from the biogas plant on the farm, such as improved manure management. In addition, both the industrial and the farm-scale plants saw new business opportunities in the future, such as biogas use as traffic fuel and recycling nutrients. Biogas technology also has potential to mitigate climate change and eutrophication. Future policies should more specifically take these benefits and possibilities into account. Highlights: Biogas has benefits that improve its value beyond energy use. The benefits are not yet fully acknowledged in and supported by Finnish policies. Currently biogas production relies on waste treatment benefits. Biogas production may become more feasible as a part of circular economy. Entrepreneurs prefer investment aids over production support.